(untitled) (Actual Problems of Psychology in Educational Institutions, 2021)
The article is devoted to the problem of emotional burnout of educators. A theoretical overview of modern concepts of the phenomenon is presented. An attempt is made to provide a detailed and definitive analysis of the basic concept. The basic essence of the phenomenon is determined as a complex psychophysiological phenomenon that occurs as a result of prolonged emotional overload, especially in the conditions of performing an activity. The polyfactorial specificity and content-dynamic features of the emotional burnout syndrome of educational workers were revealed. The need to organize socio-psychological support for the teacher’s activities is emphasized, which provides for an improvement in working conditions and an increase in the energy-adaptive potential of educators